Ethnomedicinal Uses of Medicinal Plants Used by Tribes of Valparai, Coimbatore, Tamil Nadu, India - Chanthru, Kothandapani; Gomathi, Rajkumar; Manian, Sellamuthu (Indian Forester, 2016)
Ethnobotany is gaining vitality as data on traditionally used medicinal plants are with no or very minimal side effects. The present study aims to investigate the ethnic knowledge of the tribes of Valparai. Standard questionnaires were prepared and used in this study. The data was gathered based on the oral information given by 8 tribal medicinal practitioners after repeated visits in the study area. Traditional uses of 88 plant species belonging to 46 families with their medicinal uses were collected and documented. Among them, 8 plant species that have not yet been described are included in the study. This knowledge of medicinal plants can serve as a revival of interest in the traditional folk medicine. Moreover the hidden ethnobotanical uses of both common and rare plants has to be protected and so, it adds the wealth of medicinal knowledge eventually India's pride.